377 ESTIMATING SEXUAL ACTIVITY RATES IN TEENS AND THE IMPACT ON CHLAMYDIAL SCREENING RATES: HEALTH PLAN EMPLOYER DATA INFORMATION SET ADMINISTRATIVE DATA VERSUS ANONYMOUS SURVEYS. (1st January 2005) - Tebb, K.; Ko, T.; SantaMaria, B.; Neuhaus, J.; Wibbelsman, C.; Tipton, A.; Miller, K.; Shafer, M.
Abstract : Purpose: Chlamydia trachomatis (CT) screening of sexually active girls is a performance standard in the Health Plan Employer Data Information Set (HEDIS) to monitor the quality of care in managed care organizations. There has only been one study examining the validity of the HEDIS measure to identify sexually active females and this study did not specifically report on teen data. Because of the lack of data and concern about the HEDIS measure for teens (e.g., oral contraceptive prescription use for acne & reproductive counseling as a preventive service), we compared two different methods for calculating CT screening rates among sexually active adolescent females: HEDIS vs. teens' self-report survey data. Methods: This study was implemented in 10 ambulatory pediatric departments of a large California HMO as part of a larger randomized control trial designed to increase CT screening rates among sexually active 14-18 yo adolescent females (Shafer et al. 2002) during regularly scheduled health maintenance visits (HMVs). CT screening rates are the number of CT tests done in the past 12 months for a given teen divided by the estimated number of sexually active teens. Laboratory (CT tests) and HMVs data was compiled for three years (2001-2003). Two different methods were used to estimate the number of sexually active teens. First, HEDIS administrative data was used (as specified with ICD-9 and CPT-4 codes). Second, anonymous surveys at each of the pediatric clinics were administered to calculate sexual activity rates. Results: Significantly more teens were estimated to be sexually active using the HEDIS specifications compared to self-reported survey data. The mean number of teens identified as sexually active via HEDIS across the 3 years was 337 compared to 140 using the self-reported survey data, p=0.008. Improvements in CT screening rates in intervention clinics compared to controls were detected in both methodologies; however, the difference was not as robust with the HEDIS measure. Conclusions: There are many advantages for using administrative data to estimate sexual activity used to calculate CT screening rates; however, more research is needed to examine its validity especially for the young adolescent population. This issue is extremely important, as clinicians monitor the effectiveness of their interventions to progress towards the goal of universal CT screening of sexually active females.